Construction of Conductive Network in Carbon-Nanotube-Based Nanocomposites for Electromagnetic Wave Absorption via Diameter and Composition Regulation. Issue 1 (1st January 2023) - Fang, Yuan; Wang, Wenjian; Wang, Shuai; Xue, Weidong; Zhao, Rui
Abstract: Nitrogen-doped carbon nanotubes (NCNTs) and their composites are promising electromagnetic wave absorbers for their strong dielectric polarization and tunable conductivity. However, further investigation is needed to understand the relationship between diameter, composition, and absorption performance. Herein, using the Trojan catalyst strategy in which the catalyst emerged in-situ from a solid solution, the diameter of NCNTs and the composition of the absorber composite were regulated to achieve an effective absorption bandwidth of 4.4 GHz at 1.6 mm. This study showed that the diameter of NCNTs plays a critical role in the formation of conductive network, and an insulating phase can act as a modulator of impedance.